2020
DOI: 10.1016/j.ebiom.2019.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein A2/B1 is a negative regulator of human breast cancer metastasis by maintaining the balance of multiple genes and pathways

Abstract: Background: Heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 is an important RNA-binding protein that affects the RNA processing, splicing, transport and stability of many genes. hnRNPA2/B1 is expressed during proliferation and metastasis of various cancer types and promotes such processes. However, the precise role and mechanism of hnRNPA2/B1 in breast cancer remain unclear. Methods: The association of hnRNPA2/B1 with breast cancer metastasis was assessed using tissue chips, mouse models and publicly ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
1
36
1
2
Order By: Relevance
“…The significant association among the hnRNP family members and clinicopathological features and survival outcomes of patients with cancer has been confirmed, indicating that hnRNPs are novel and promising cancer therapeutic targets and predictive biomarkers for treatment response and prognostic evaluation [ 16 , 26 31 ]. In BRCA, the hnRNP family members, including HNRNPA2B1, HNRNPC, HNRNPH1, HNRNPK, HNRNPM, and PTBP1, function as oncogenes in BRCA progression [ 7 , 8 , 18 , 32 36 ]. Liu et al reported that HNRNPA2B1 is a negative regulator of BRCA metastasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant association among the hnRNP family members and clinicopathological features and survival outcomes of patients with cancer has been confirmed, indicating that hnRNPs are novel and promising cancer therapeutic targets and predictive biomarkers for treatment response and prognostic evaluation [ 16 , 26 31 ]. In BRCA, the hnRNP family members, including HNRNPA2B1, HNRNPC, HNRNPH1, HNRNPK, HNRNPM, and PTBP1, function as oncogenes in BRCA progression [ 7 , 8 , 18 , 32 36 ]. Liu et al reported that HNRNPA2B1 is a negative regulator of BRCA metastasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In BRCA, the hnRNP family members, including HNRNPA2B1, HNRNPC, HNRNPH1, HNRNPK, HNRNPM, and PTBP1, function as oncogenes in BRCA progression [ 7 , 8 , 18 , 32 36 ]. Liu et al reported that HNRNPA2B1 is a negative regulator of BRCA metastasis [ 36 ]. Hu et al revealed that HNRNPA2B1 knockdown inhibits cell proliferation, induces apoptosis, and prolonges the S phase of the cell cycle in MCF-7 and MDA-MB-231 cells via the STAT3 and ERK1/2 signaling pathways [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of pDCs contributed to higher killing efficacy of effector lymphocyte in TME of breast cancer model, including FLT3L-induced pDCs [ 120 , 121 ]. In yet another study, simultaneous inhibition of STAT3 and Tcf4 signaling pathways was reported to suppress the breast cancer cells metastasis both in vitro and in vivo [ 122 ]. Despite insufficient evidence, FLT3L/STAT3 cascade directly conducted pDC and anti-tumor immunity via Tcf4 in breast cancer.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Epithelial–mesenchymal transition (EMT) accelerates the progress of tumor metastasis [ 85 ]. Liu et al [ 86 ] demonstrated that hnRNPA2B1 inhibits EMT and metastasis in breast cancer by directly binding to PFN2 mRNA and reducing its stability. Conversely, eIF3m promotes breast cancer cell migration and invasion by activating EMT [ 71 ].…”
Section: A Modification In Breast Cancermentioning
confidence: 99%